PENGARUH AKTIVITAS MELIHAT DEKAT TERHADAP TAJAM PENGLIHATAN PADA MURID SEKOLAH MENENGAH PERTAMA DI KECAMATAN JATINANGOR - Raisha Pratiwi Indrawati; Reni Farenia; Mayasari Wahyu Kuntorini (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2020)
Near work activity was estimates as risk factor of refractive error. This study aimed to analyze the association between near work activity and visucal acuity in junior high school students in Jatinangor. This study used cross-sectional method. Total of 147 subjects were screened for visual impairment and assessed for near work activities. Result showed total diopter-hours and time spent for each near work activity was less in group with visual acuity ≥ 6/18 than < 6/18 with no significant difference, except for playing games (p=0.018). In conclusion, near work activity does not have impact on visual acuity, except for playing games.